HOSPITAL DENTISTRY: THE NEW DENTAL SPECIALTY THAT RATIFIES THE IMPORTANCE OF THE DENTAL SURGEON IN INTENSIVE CARE UNITS - Barros, Maria Izabella Marques (2024)
Hospital Dentistry is the new dental specialty that works to promote the oral health of individuals who require assistance in hospital, benefiting the homeostasis of the patient's general health. The objective of this study was to discuss the importance of the dentist in the multidisciplinary team in the intensive care units (ICU) through a cross-sectional and qualitative study, which used a questionnaire, as a research instrument, applied to a sample of 15 dentists working in the ICU of public and private hospitals in Pernambuco. The data obtained were subjected to descriptive statistical analysis. Regarding the professional's role in the ICU, around 93.3% of the participants considered the presence of oral lesions in hospitalized patients to be common and 66.7% classified the patients' oral condition as  unfavorable. Regarding the presence of dentists in the hospital, most professionals (73.3%) stated that profession still does not have due recognition. The data obtained in this study confirmed the importance of the dentists' role in preventing and promoting the health of patients admitted to the ICU and highlighted the lack of recognition of the presence of those professionals in hospitals.